ROLE OF AI-ENABLED GAMIFICATION IN ENHANCING LEARNING MOTIVATION AMONG UNIVERSITY STUDENTS - Jain, Manisha; Saini, Neha; Chopra, Aarti (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Artificial Intelligence and Gamification has emerged as a new trend in the education sector. They have transformed the learning style and pattern of students. In the past, students learned through traditional methods in which they feel boredom and less interest in participation. The evolution of learning and teaching methods in which AI and Gamification has integrated drives innovation and modernization in the sector. This research study aims to evaluate the role of AI-enabled Gamification in enhancing the learning motivation of students in higher education. Along with this, the study also finds that these modern technologies help in increasing participation of students and keep them more engaged and motivated towards learning. The research study follows a quantitative research design in which data is collected from university students and analyzed. The data and facts make the research more accurate. Various past research has done the AI integration in learning and gamification in learning, but the phenomenon of AI-Enabled Gamification remains unexplored. This research study highlights the role of AI-Enabled Gamification in learning in higher education and evaluates how they improve the learning experience of students and keep them motivated towards learning.